Association of individual and work-related risk factors with musculoskeletal symptoms among Iranian sewing machine operators. (November 2015) - Dianat, Iman; Kord, Madeh; Yahyazade, Parvin; Karimi, Mohammad Ali; Stedmon, Alex W.
Abstract: This cross-sectional study evaluated working conditions and the occurrence of self-reported musculoskeletal symptoms among 251 Iranian sewing machine operators. A questionnaire and direct observations of working postures using the rapid upper limb assessment (RULA) method were used. A high prevalence of musculoskeletal symptoms, particularly in the neck/shoulders, back and hands/wrists were found. The mean RULA grand score of 5.7 highlighted a poor sewing workstation design and indicated that most operators (with posture assessed at action level 3) needed an investigation and changes in their working habits soon. Work-related factors (including number of years worked as an operator, prolonged working hours per shift, long duration of sitting work without a break, feeling pressure due to work and working postures) and individual factors (including age, gender, BMI and regular sport/physical activities) were associated with musculoskeletal symptoms in multiple logistic regression models. The findings add to the understanding of working conditions of those jobs involving sewing activities and emphasise the need for ergonomic interventions to reduce musculoskeletal symptoms in the future. Highlights: Prevalence and severity of musculoskeletal symptoms (MSDs) was high among operators. The relatively high RULA scores highlighted a poor sewing workstation design. Both physical and psychosocial job factors were associated with MSDs.